Association between maternal COMT gene polymorphisms and fetal neural tube defects risk in a Chinese population. Issue 1 (31st December 2013) - Liu, Jufen; Wang, Linlin; Fu, Yunting; Li, Zhiwen; Zhang, Yali; Zhang, Le; Jin, Lei; Ye, Rongwei; Ren, Aiguo
Background: Maternal tea consumption was reported to increase the risk of fetal neural tube defects (NTDs). Catechol‐O‐methyltransferase (COMT) may be involved in the metabolism of polyphenolic methylation of tea, thus influence the risk of fetal NTDs. Methods: A total of 576 fetuses or newborns with NTDs and 594 healthy newborns were included in the case–control study. Information on maternal tea consumption, sociodemographic characteristics, reproductive history, and related behavior was collected through face‐to‐face interviews. Maternal blood samples were collected to examine polymorphisms in COMT, and the possible interaction of COMT and tea consumption was analyzed. RESULTS: After controlling for potential confounders, homozygotes of rs737865 showed an elevated risk for total NTDs (odds ratio [OR] = 2.04, 95% confidence interval [CI], 1.24–3.35) and for the anencephaly subtype (OR = 1.99, 95% CI, 1.17–3.39). The CC genotype of rs4633 was positively associated with the overall risk of NTDs (OR = 3.66, 95% CI, 1.05–12.83). Heterozygotes for rs4680 were associated with a decreased risk of spina bifida (OR = 0.71, 95% CI, 0.51–0.98). The COMT rs4680 A allele was negatively related with the risk of spina bifida, with adjusted OR = 0.64 (95% CI, 0.45–0.89). An interaction between tea consumption (1 to 2 cups/day) and the rs4680AA/AG genotype was found in the spina bifida subtype (Pinteraction = .08). Conclusion: Several COMT variants were associated with elevated risk of NTDs in a Chinese population. Maternal tea consumption may be associated with an increased risk for fetal NTDs in genetically susceptible subgroups. Birth Defects Research (Part A) 100:22–29, 2014. © 2013 Wiley Periodicals, Inc.